Revisiting the Eoarchean Akilia quartz-pyroxene rock with potassium isotopes: Implications for early-ocean sedimentation - Zheng-Yu Long; Frédéric Moynier; Wei Dai; Mark van Zuilen; Jun Deng; Kun-Feng Qiu (Proceedings of the National Academy of Sciences, 2025)
The Eoarchean quartz-pyroxene rock from Akilia Island in Greenland has been proposed as one of Earth’s oldest banded iron formations (BIF) and a potential host for the earliest biosignatures. However, the origin of its protolith, whether it metamorphosed from an igneous or sedimentary precursor, remains debated. Here, we revisit this longstanding Akilia controversy using potassium isotope analyses, comparing Akilia samples with BIFs and black shales spanning the Eoarchean to Mesoproterozoic. Our results demonstrate that BIFs and black shales show systematic potassium isotope variations correlated with their potassium contents. Potassium-poor BIF layers display heavier isotopic compositions close to seawater values, whereas clay-rich layers exhibit elevated potassium contents and lighter isotopic signatures. The Akilia quartz-pyroxene rock was initially characterized by low potassium concentrations and heavy potassium isotopic compositions consistent with chemical sediments deposited from ancient seawater. It was subsequently modified by metasomatic fluids derived from nearby metamorphosed igneous rocks. These findings support a sedimentary origin for the Akilia quartz-pyroxene rock. Furthermore, our study provides an isotopic framework for interpreting ancient oceanic environments and offers insights into the potassium cycling and habitability of early Earth.